2020
DOI: 10.1007/s10067-020-05282-2
|View full text |Cite
|
Sign up to set email alerts
|

Lower risk of primary Sjogren’s syndrome in patients with dengue virus infection: a nationwide cohort study in Taiwan

Abstract: The data concerning the association between dengue viruses (DV) infection and autoimmune diseases (ADs) remain unclear and are scarce. This nationwide population-based cohort study assessed the risk of ADs among patients with DV infection. We analyzed Taiwanese medical data from the Registry of the National Notifiable Disease Reporting System of Taiwan's Centers for Disease Control between 1998 and 2015 and identified patients with DV infection. From the entire general population data in the National Health In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
3
3
0
Order By: Relevance
“…The upregulated common DEGs were enriched in KEGG terms associated with immune-related pathways and infection-related pathways, including the T cell receptor and B cell receptor signaling pathways. GO terms implicated in pSS pathogenesis include immune system process (38), T cell activation (39-41), B cell activation (42,43), and response to virus (44,45). Previously reported pSS-related genes, including HLA-DRA (8,46), CCL19 (47,48), CXCL9 (49), and CD3D (50), were enriched in our study, suggesting that the related common DEGs are potential biomarkers for pSS.…”
Section: Discussionsupporting
confidence: 51%
“…The upregulated common DEGs were enriched in KEGG terms associated with immune-related pathways and infection-related pathways, including the T cell receptor and B cell receptor signaling pathways. GO terms implicated in pSS pathogenesis include immune system process (38), T cell activation (39-41), B cell activation (42,43), and response to virus (44,45). Previously reported pSS-related genes, including HLA-DRA (8,46), CCL19 (47,48), CXCL9 (49), and CD3D (50), were enriched in our study, suggesting that the related common DEGs are potential biomarkers for pSS.…”
Section: Discussionsupporting
confidence: 51%
“…Inconsistent with the findings of our study, a recent cohort study conducted by Chang CC et al reported a decreased risk of primary SS development after dengue infection ( 11 ). The authors excluded patients who were diagnosed with autoimmune diseases within1 year before the diagnosis of dengue infection to confirm the diagnosis of primary SS ( 11 ).…”
Section: Discussionsupporting
confidence: 86%
“…The authors found that the risk of SLE for patients in the dengue group was significantly higher than that of patients in the non-dengue control group ( 3 ). Few studies have investigated the influence of dengue on the development of autoimmune diseases ( 10 , 11 ). However, to the best of our knowledge, no population-based, case-control study assessed the association between dengue infection and the risk of SARDs.…”
Section: Introductionmentioning
confidence: 99%
“…Inconsistent with the findings of our study, a recent cohort study conducted by Chang CC et al reported a decreased risk of primary SS development after dengue infection (11). The authors excluded patients who were diagnosed with autoimmune diseases within1 year before the diagnosis of dengue infection to confirm the diagnosis of primary SS (11). However, given that some primary SS patients may present with other autoimmune diseases, such as Hashimoto's thyroiditis and immune thrombocytopenia purpura, before the diagnosis of SS, the exclusion of patients with other autoimmune diseases before the onset of dengue may lead to an underestimation of the incidence of primary SS in patients with dengue.…”
Section: Discussionsupporting
confidence: 86%
“…The authors found that the risk of SLE for patients in the dengue group was significantly higher than that of patients in the nondengue control group (3). Few studies have investigated the influence of dengue on the development of autoimmune diseases (10,11). However, to the best of our knowledge, no population-based, case-control study assessed the association between dengue infection and the risk of SARDs.…”
Section: Introductionmentioning
confidence: 99%